Sistem Pemantauan Postur: Pendeteksi Durasi Bungkuk dan Postur Tubuh Berbasis IoT - Aan Febriyansyah; Misri Yandi; Rizky Daffa Pratama; Tio Pratama (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
The main risk factors for non-communicable diseases (NCDs), particularly low back pain (LBP), which affects 18.1% of the population in Indonesia, are prolonged sitting and lack of physical activity.  The aim of this study was to develop an Internet of Things (IoT)-based system that can detect sitting duration and body posture to help people maintain ergonomic posture and regulate their sitting time.  This system uses an ESP32 microcontroller with a flex sensor and HY-SRF05 ultrasonic sensor to identify the user's presence.  To enable remote monitoring via a web application, sensor data is displayed on an I2C LCD and sent to a Firebase real-time database. A buzzer provides a warning when a person bends over (angle greater than 32.7°) or sits for longer than the set time.  Test results show that the system can accurately distinguish between normal posture (9°-15°) and slouching (32°-80°). The ultrasonic system records and stores data history in real-time via Firebase, enabling analysis of user posture trends and sitting duration. The sensor accuracy rate is 98.63% with an average error of 1.37%.  By adding historical data monitoring, smartphone notifications, and cloud-based data logger features, this system shows significant improvement over previous tools, although the timer test had an average time of 820 seconds. Further development is recommended to improve timer accuracy and user convenience by adding a wireless belt and a separate RTC module